Karakteristik fenotip Kambing Kacang di Desa Malangrejo, Kecamatan Banyuurip Kabupaten Purworejo : Phenotypic characteristics of Kacang Goats in Malangrejo Village, Banyuurip District, Purworejo Regency - Prasetya, Aditya; Jati, Wahyu Damar; Fredyawan, Fuad; Ahmadilla, Agil Akhsan; Rohman, Jody Aditya; Mudawaroch, Roisu Eny (Jurnal Riset Agribisnis dan Peternakan, 2023)
The Kacang goat was a goat native to Indonesia which has high adaptability to local natural conditions and has a very high reproductive power. Developing a livestock business was by studying the performance of goats. The aim of the research was to determine the performance of Kacang Goats, body weight and body size index of Kacang Goats. The research material was Kacang goats. The research variables were horn length, ear length, chest circumference, chest width, shoulder height, chest circumference, body length, tail length, leg height, body weight and body size index (IUT). The results showed that the horn length was 9 ± 1.35 cm (females), 6.25 ± 1.60 cm (males). Ear length 22.75 ± 0.85 (females), 21.00 ± 1.29 (males). Chest circumference 71.25 ± 2.72 cm (females) and 68.75 ± 1.97 cm (males). Chest width 19.5 ± 2.59 cm (females), 16.00 ± 1.08 cm (males). Tail length 22.75 ± 0.85 cm (females) 21.00 ± 1.29 cm (males). Leg length (females) 51 ± 3.18 cm, 46.25 ± 1.65 cm (males). The body weight of female livestock was 35.73 ± 3.16 kg, while for male livestock it was 30.04 ± 1.64 kg. The body size index for female goats was 0.99 ± 0.05 and for female males was 0.93 ± 0.04. The conclusion that the performance of female Kacang goats was greater than the performance of female Kacang goats includes: horn length, ear length, chest circumference, chest width, body length, tail length and leg length. The body weight and body size index of female goats are higher than male goats.